1975
DOI: 10.1093/infdis/132.6.685
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Response to Acute Otitis Media in Children. II. Serum and Middle Ear Fluid Antibody in Otitis Media Due to Haemophilus influenzae

Abstract: The antibody response in serum and middle ear fluid was studied in 40 children less than two years of age who had otitis media due to Haemophilus influenzae. Specific antibody in serum was determined by either a bacteriocidal test or an indirect fluorescent antibody test, and in the middle ear fluid by the latter test. For both assays the infecting bacterium of the patient was used. Half of the acute sera and three-fourths of the convalescent sera had antibody of at least one of the IgG, IgM, or IgA classes; I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 10 publications
4
21
1
Order By: Relevance
“…The incidence of culture-positive effusions from the contralateral unchallenged ears (bilateral effusion) was 5% in the group challenged with wt BCH-3 and 62% in the group challenged with the isogenic BCH-3 ompP1 mutant on days 6 and 8 (P ϭ 0.0045). (71,72). These results are paralleled by our study of an adult patient indicating that the majority of serum bactericidal antibody activity after recovery from NTHI disease was directed to OMPs (24).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The incidence of culture-positive effusions from the contralateral unchallenged ears (bilateral effusion) was 5% in the group challenged with wt BCH-3 and 62% in the group challenged with the isogenic BCH-3 ompP1 mutant on days 6 and 8 (P ϭ 0.0045). (71,72). These results are paralleled by our study of an adult patient indicating that the majority of serum bactericidal antibody activity after recovery from NTHI disease was directed to OMPs (24).…”
Section: Discussionsupporting
confidence: 71%
“…Disease in infants typically begins after maternal antibodies have dissipated and before their own immune systems are fully matured (42) (15) are efficacious, unencapsulated NTHI remains responsible for ϳ30% of the Ͼ45 million episodes of acute bacterial otitis media yearly in North America and Europe (43,45,58,68) and is implicated in as many as ϳ20% of the 4 million fatal acute respiratory infections per annum worldwide occurring mostly in children (9). Studies of these infections demonstrate that NTHI usually elicits bactericidal antibodies (71,72). However, protection appears to be strain specific, with a P values are based on a comparison of data for chinchillas immunized with rP1 plus adjuvant with those for chinchillas immunized with adjuvant alone, as determined by the Fisher exact test (80).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators published two elegant studies in the 1970s that strongly suggested local production of pathogen-specific antibodies was occurring in the middle ear space of children with AOM (7,28). Our results are not inconsistent with their observations since they did not investigate the possibility that the origin of the pathogen-specific antibodies identified in the middle ear space of children with AOM were not from local production but rather from reflux of nasopharyngeal secretions.…”
Section: Discussioncontrasting
confidence: 54%
“…Although the sensitivity of the antibody assay varied among the different immunoglobulin classes, the differences were insufficient to account for the degree of dominance of the IgG type of antibody. Specific immunoglobulins of the G, M, and A classes have been identified previously in MEF of children with pneumococcal and H. influenzae OME; organism-specific IgG antibody was similarly the more common immunoglobulin class detected in both types of infection (22,23).…”
Section: Resultssupporting
confidence: 54%